2012
DOI: 10.1136/bmjopen-2012-001465
|View full text |Cite
|
Sign up to set email alerts
|

HIV among people who inject drugs in Central and Eastern Europe and Central Asia: a systematic review with implications for policy

Abstract: Background and objectivesHIV among people who inject drugs (PWID) is a major public health concern in Eastern and Central Europe and Central Asia. HIV transmission in this group is growing and over 27 000 HIV cases were diagnosed among PWID in 2010 alone. The objective of this systematic review was to examine risk factors associated with HIV prevalence among PWID in Central and Eastern Europe and Central Asia and to describe the response to HIV in this population and the policy environments in which they live.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 106 publications
3
76
0
5
Order By: Relevance
“…We find that published epidemiological research lacks explicit focus in delineating structural risk factors potentially indirectly linked to HIV among FSWs, and note the need to better develop such measures. There is a similar tendency regarding research investigating HIV risk factors among PWID 2. Our review thus reiterates the need for improving the extent to which epidemiological studies seek to develop measures of social and structural context.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We find that published epidemiological research lacks explicit focus in delineating structural risk factors potentially indirectly linked to HIV among FSWs, and note the need to better develop such measures. There is a similar tendency regarding research investigating HIV risk factors among PWID 2. Our review thus reiterates the need for improving the extent to which epidemiological studies seek to develop measures of social and structural context.…”
Section: Discussionmentioning
confidence: 75%
“…Figure 1 summarises the papers searched and retained in the review. Following full-text review 73 peer-reviewed and grey literature documents were identified as meeting our criteria of which 63 papers provided unique estimates of HIV and STI prevalence and nine papers report multivariate or univariate2 risk factors for HIV/STI among FSWs.…”
Section: Methodsmentioning
confidence: 99%
“…Based on a systematic review of Central and Eastern Europe and Central Asia literature, heroin is reported as the main drug in Central Europe [21]. Russia [22], Ukraine [23] and Moldova [24] report injection of homemade opioids alongside heroin.…”
Section: Discussionmentioning
confidence: 99%
“…Police targeting, required "name-based" registers for drug treatment and HIV services, and mistreatment by the medical establishment hinder PWID health seeking behaviors, access to prevention and care services (Izenberg and Altice, 2010;Krusi et al, 2010;Mimiaga et al, 2010), use of drug treatment services, and enrollment in OST programs (Boltaev et al, 2012a(Boltaev et al, ,b, 2013. A review of studies from Eastern Europe and Central Asia reported that between half and three-quarters of PWID have experienced an arrest (Jolley et al, 2012). Incarceration of PWID also pose specific threats for those with HIV infection due to interruptions in care and treatment .…”
Section: Current Context Of Hiv Services For Pwid In Central Asiamentioning
confidence: 95%